PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL QUANTUM TEACHING DAN MEDIA PALANG ARAHKU - Dwi Wijayanti; Murtono Murtono; Lintang Kironoratri (WASIS : Jurnal Ilmiah Pendidikan, 2020)
This study aims to describe the improvement of learning outcomes (knowledge and skills) as well as the teaching skills of fourth grade teachers at SDN 1 Gondoharum on theme 6 My goals by using Quantum teaching learning models assisted by PALANG ARAHKU. The type of research is Classroom Action Research. This research was conducted with 27 research subjects and teachers which lasted for 2 cycles. Each cycle consists of 4 stages, namely planning, implementation, observation, and reflectionThe results of the study in the first cycle of the knowledge domain of IPS and Indonesian students in classical terms gained 68.7% (good). Then it increased in cycle II to 86.99% (very good). In the realm of skill cycle I gained a percentage of 71.5% (good) increased in cycle II to 87.5% (very good). The results of teacher teaching skills have increased. In cycle I gained a percentage of 71% (good) and cycle II increased to 85% (very good). Based on the results of cycle I and cycle II of the Quantum teaching model of grade IV students at SDN 1 Gondoharum Kudus.